A Superhydrophobic Moso Bamboo Cellulose Nano-Fibril Film Modified by Dopamine Hydrochloride - Wu, Yan; Zhao, Wanying; Wu, Xinyu; Gan, Jian; Zhang, Haiqiao; Cai, Yijing (Frontiers in Bioengineering and Biotechnology, 2021)
The moso bamboo fiber powder was used as raw material to prepare cellulose nano-fibril films, 5% of polyvinyl alcohol solution was used as a structural reinforcement agent, dopamine hydrochloride (DA) was used as a surface adhesive, and hexadecyl trimethoxy silane was used as a surface modifier. The superhydrophobic films were prepared by vacuum filtration and impregnation. The results showed that the water contact angle on the surface of the film could reach 156°. The microstructure and chemical composition of the film surface was further studied by scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FTIR), and roughness measurement The scanning electron microscopy images showed that the nanofibers on the surface of Cellulose nanofibers film were arranged and randomly distributed, thus forming a dense network interwoven structure. In PDA hydrophobic modification solution, an Hexadecyltrimethoxysilane was hydrolyzed to a hexadecyl silanol to obtain the polar terminal hydroxyl of Hexadecyl silanol molecule. The -OCH3 terminal group of HDTMS reacted with hydroxyl/H2O to form a silanol (Si-OH) bond and further condensed to form a Si-O-Si network. In addition, due to the hydrophilicity of the surface of the nano cellulose film, a large amount of—OH was adsorbed on the surface of the nano cellulose film, resulted in the chemical connection between cetyl groups, thus realized the grafting of cetyl long-chain alkyl groups onto the fibers of the nano cellulose film.The film showed good self-cleaning and waterproof properties, which can be widely used in wet environment packaging and building.